Persepsi Mahasiswa Terhadap Penggunaan E-Learning Sebagai Media Pembelajaran Yang Telah Diterapkan Di Universitas Negeri Makassar - Asis Nojeng; Arya Putra Abshari; Deswanto Richard Sirenden; Muhammad Rifqi Alsadhani; Muhammad Fardhan (Sakura Digital Nusantara, 2023)
E-Learning is one of the learning media that has been widely used during the COVID-19 pandemic. E-Learning is innovation that would is used in learning, not only for learning material but also a change in the various competence students. E-Learning is very potential to make learning rocess more effective because student chance to have an interaction with lecturers, classmate, or lecture material is wider. Student can communicates with lecturer anytime by e-mail and chat. The way of communication can be choiced, synchronus or asynchronus. With E-Learning, student can learns although he does not present at class physically. Learning process goes by interaction student and lecture materials that avaiable and can be accessed via internet. The flexibility of learning activity is happened by used of computer and internet technology. On this case, to join with E-Learning, spesial software does not added for computer used. The main thing is connected to internet. E-Learning makes it easy for students to take part in learning wherever and whenever. This study aims to determine student perceptions of using E-Learning as a learning medium during learning from home at Makassar State University